At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Y = 3x -1. Y = 3x - 1
(-3) Y = x - 7. -3y = -3x + 21
-2y = 20
-2. = -2
Y = - 10
Y = 3x - 1
-10 = 3x - 1
+ 1. + 1
-9. = 3x
3. 3
-3 = x
(-3,-10)
(-3) Y = x - 7. -3y = -3x + 21
-2y = 20
-2. = -2
Y = - 10
Y = 3x - 1
-10 = 3x - 1
+ 1. + 1
-9. = 3x
3. 3
-3 = x
(-3,-10)
Solution : {y,x } = { -10 , -3 }
Solve the equation [2] for the variable of y
2 . Y = x-7
Plug this in for variable y in the equation [1]
1 (x -7 ) -3x = -1
1 -2x = 6
Solve the equation [1] for the variable x
1 2x =-6
1 x= -3
By now we know this much
Y = x-7
X =-3
Use the x value to solve for y
Y= ( -3 ) -7 = -10
Solve the equation [2] for the variable of y
2 . Y = x-7
Plug this in for variable y in the equation [1]
1 (x -7 ) -3x = -1
1 -2x = 6
Solve the equation [1] for the variable x
1 2x =-6
1 x= -3
By now we know this much
Y = x-7
X =-3
Use the x value to solve for y
Y= ( -3 ) -7 = -10
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.